Minimum Wages and Firm Value - Brian Bell; Stephen Machin (Institute for the Study of Labor (IZA), 2016)
How does the value of a firm change in response to a minimum wage hike? The evidence we have to date is not well-suited to answer this question, principally because events that have been studied are not completely unknown to the stock market or have uncertainty associated with them. This paper exploits the announcement of a sizeable change in the minimum wage in the UK that was both totally unanticipated and free of uncertainty. The stock market response of employers of minimum wage workers is examined in an event study setting, looking at minute-by-minute changes surrounding the announcement and at cumulative abnormal returns on a daily basis before and after the announcement. The analysis uncovers significant falls in the stock market value of low wage firms. The size of the fall in value is compared to the fall in profitability in response to the wage cost shock that will be induced by the announcement and is seen to be of a comparable magnitude.
Keywords: J23; L25; 330; minimum wages; firm value